1 Answer | Add Yours
To eliminate the logarithm, apply the rule `e^(lnx)=x` .
Express the equation in quadratic form `ax^2+bx+c=0` .
Set each factor to zero and solve for x.
`x+2=0` and `x=0`
Then, substitute the values of x to the original equation to check.
`x=-2` , `ln (-2*-2) = ln(-2)^2`
`ln4 = ln4` (True)
`x=0 ` , `ln(-2*0)= ln(0)^2`
`ln 0 = ln 0` (Invalid logarithm)
Note that in logarithm, we cannot have a zero as the argument. It should always be greater than zero.
Hence, the solution to the equation `ln(-2x)=lnx^2` is `x=-2` .
We’ve answered 319,208 questions. We can answer yours, too.Ask a question